Hubungan Burnout Perawat dengan Sikap Perawat Tentang End Life Care di Ruang Intensive Care RSUD Sumedang - Neng Inggri Fitriya; Popon Haryeti; Ayu Prameswari Kusuma Astuti (Malahayati Nursing Journal, 2024)
ABSTRACT The care provided in intensive care rooms such as the ICU and NICU focuses on life-saving care for critical patients. For some patients who show no hope of life, nurses are required to provide end life care. The high workload of nurses in intensive care rooms can cause nurses to be vulnerable to burnout, which can have a negative impact on nurses' attitudes in providing care services. Therefore, this research aims to determine the description and relationship between nurse burnout and nurses' attitudes about end life care in the intensive care room at Sumedang Regional Hospital. This research was conducted using a correlational design and a cross-sectional approach. Data collection was carried out by distributing questionnaires to respondents. The number of respondents was 57, determined based on a total sampling technique from the entire population of nurses working in the intensive care room. The normality test shows that the data is normally distributed, so the Pearson correlation test is used for bivariate analysis with the JASP statistical analysis program. The correlation test results showed that the coefficient was -0.092, and the p-value was 0.05, namely 0.495. So, there is no significant relationship between nurse burnout and nurses' attitudes about end life care in the intensive care room at Sumedang Regional Hospital. Keywords: Burnout, Attitude, End Life Care  ABSTRAK Perawatan yang diberikan di ruang intensive care seperti ICU dan NICU cenderung fokus pada perawatan life saving untuk pasien kritis. Pada beberapa pasien yang menunjukkan tidak adanya lagi harapan hidup, maka perawat wajib memberikan perawatan menjelang ajal atau end life care. Tingginya beban kerja perawat di ruang intensive care dapat menyebabkan perawat rentan mengalami burnout sehingga dapat berdampak negatif terhadap sikap perawat dalam memberikan pelayanan perawatan. Oleh karena itu tujuan dari penelitian ini adalah untuk mengetahui gambaran serta hubungan antara burnout perawat dengan sikap perawat tentang end life care di ruang intensive care RSUD Sumedang. Penelitian ini dirancang dengan desain korelasional dan pendekatan cross sectional. Pengumpulan data dilakukan dengan menyebar kuesioner pada responden. Responden berjumlah 57 orang yang ditentukan berdasarkan teknik total sampling dari seluruh populasi perawat yang bertugas di ruang intensive care. Uji normalitas menunjukkan bahwa data bersebaran normal sehingga uji kolerasi Pearson digunakan untuk analisis bivariat dengan program analisis statistik JASP. Hasil uji kolerasi didapatkan nilai koefisien kolerasi -0,092 dan nilai p value 0,05 yaitu 0,495. Maka dapat disimpulkan bahwa tidak terdapat hubungan yang signifikan antara tingkat burnout perawat dengan sikap perawat tentang end life care di ruang intensive care RSUD Sumedang. Kata Kunci: Burnout, Sikap, End Life Care